KEMAMPUAN MEMAHAMI FAKTA DAN OPINI DALAM TEKS EDITORIAL SISWA KELAS XI SMAN 001 KAMPAR UTARA KECAMATAN KAMPAR UTARA KABUPATEN KAMPAR - Annisa, Dini; Mustafa, M Nur; Nursal, Hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study investigated the ability to understand the facts and opinions in the editorial text class XI student of SMAN 001 North Kampar Kampar District Northern District Kmpar. This study aims to determine the ability to understand the facts and opinions in the editorial text class XI student of SMAN 001 North Kampar Kampar districts Northern District of Kampar and the ability to understand the opinion editorial texts class XI student of SMAN 001 North Kampar Kampar Kampar District North District. This research is descriptive-quantitative. This research data is data from test-taking ability to understand the facts and opinions in the editorial text class XI student of SMAN 001 North Kampar Kampar District Kampar regency north. Instruments in this research is a form of objective test of the facts and opinions in the editorial text class XI student of SMAN 001 North Kampar Kampar Kampar District North District. The data collection was done by using the test. The population in this study were 125 students with the determination of a sample of 97 students. Data were analyzed with descriptive methods. The validity of the data obtained through the method of data validation. Results of this study of the test results the ability to understand the facts and opinions in the editorial text class XI student of SMAN 001 North Kampar Kampar Kampar District North District. Viewed from the aspect of understanding the facts obtained by the average value of 71.83 by the middle category. Then, from the aspect of opinions obtained an average value of 64.82 with a low category.Key Words: Editorial Text, Facts, Opinions.